PENGARUH STRUKTUR ASET, PROFITABILITAS, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Seba, Melviyana; Jonnardi, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of asset structure, profitability, and liquidity on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The sample selection technique used isprobability random sampling with the type of simple random sampling. From the sample selection technique, there are 51 manufacturing companies that will be sampled in this study. Data collection was carried out using Microsoft Excel 2019 and data processing was carried out with software or the Eviews 12 program. The test results obtained in this study showed that asset structure had a negative and significant effect on capital structure, profitability had a positive and significant effect on capital structure, and liquidity. not significantly negative on the capital structure. The implication of this study is the need for good management in funding a company to get a good capital structure that will bring a good signal for investors.